HEAT SHOCK PROTEINS AS BIOMARKERS OF FISH POLLUTION - Оnyskovets М.; Panas, N.; Lopotych, N.; Ivankiv, M.; Salamakha, I. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
Нeat Shock Proteins (HSP) belong to the natural biomarkers, which are important indicators for animal diseases diagnostics and / or instrument of analyzing the effects on organism of the habitat deteriorating factors. The contamination of water by heavy metals has adverse effect on fish organism. Even in a small quantity, such heavy metal as lead is very dangerous. The analysis of toxic effects of the lead ions on the level of expression of such heat shock proteins as HSP60, HSP70 and HSC70 family in leukocytes, liver, brain and gills of the scaly carp was the main goal of our investigation. During 96 hours the fish were kept in the aqueous environment of a tank which additionally was supplemented with Pb (CH3COO)2. The control group of fish was maintained for the similar period of time under the same conditions, without lead acetate supplementation. Concentration of HSP60, HSP70 was determinated by the dot-blot-analysis due to application of monoclonal antibodies against heat shock proteins SAB4501464 (Sigma, USA), [5A5] (ab2787) (Abcam, USA) and [1B5] (ab19136) (Abcam, USA). Detection of immune complexes was performed by using the commercial substrate solution for alkaline phosphatase - CDP-Star (Tropix, UK). Visualization was done by using X-ray film ECL HyperFilm (Amersham, USA) and a kit for films developing (Kodak). The images were processed using the software package GelPro (Version 3.1, USA). The significant dose-depended increase (p<0,001) in all experimental groups of HSP60 and HSP70 concentrations in leukocytes, liver, gill and brain has been detected, applying dot-blot analysis. At the same time, significant changes in expression of HSC70 protein have not been established. It is the evidence that stress-proteins are the sensitive markers of toxic effects of excessive concentration of lead.